Project-Based Learning untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi pada Mata Pelajaran Bahasa Arab - Ali Mufti (Universitas Negeri Jakarta, 2022)
Critical thinking is one of the 21st century skills that students must master. One way to improve students' critical thinking skills is by learning that accommodates High Order Thinking Skills (HOTS). The HOTS level is in the cognitive aspect; evaluate, analyze and create. The curriculum for Arabic subject learning has been regulated by the Decree of the Indonesian Minister of Religion number 183 and 184 of 2019, which stated that teachers are asked to direct Arabic subject learning that focuses on High Order Thinking Skills (HOTS). This study is descriptive qualitative research, describing Arabic subject learning using the Project-based learning (PjBL) model. This study describes the PBL model that can be applied to Arabic learning at Madrasah Aliyah for ten graders with the steps of; asking basic questions, planning and scheduling, monitoring, product assessment, and evaluation.